THE IMPACT OF HUMAN RESOURCES INFORMATION SYSTEMS IN IMPROVING THE TRAINING PROCESS IN INDUSTRIAL FIRMS: - AQABA CASE STUDY - Hayajneh, Omar (mohamad raouf); Al-Omari, Burhan M Awad; Al-Mobaideen, Hisham Othman; Allahawiah, Sattam Rakan (European Scientific Journal, ESJ, 2012)
This study aimed to describe the impact of human resources information systems in identifying training needs, defining the goals of training programs, the implementation of training and evaluation and follow-up the effectiveness of training in industrial enterprises in Aqaba city , the study found that there was a link between human resources information systems and between training needs, defining the goals of training programs, the implementation of training and evaluation and follow-up the effectiveness of training in industrial enterprises in Aqaba city. The most important recommendation of the study was that the responsible people of human resources information systems in industrial firms in the city of Aqaba should make it capable of selecting training needs on the company in the long term, to identify individual needs, measure goals through training programs, overcome the difficulty in dealing with the human resources management information system at the implementation of training programs, and the need to use standard tools to observe the behavior of the workers after the implementation of training programs.